Higher Mitochondrial Respiration and Uncoupling with Reduced Electron Transport Chain Content in Vivo in Muscle of Sedentary Versus Active Subjects - Conley, Kevin E.; Amara, Catherine E.; Bajpeyi, Sudip; Costford, Sheila R.; Murray, Kori; Jubrias, Sharon A.; Arakaki, Lori; Marcinek, David J.; Smith, Steven R. (The journal of clinical endocrinology and metabolism, 2013)
Objective:This study investigated the disparity between muscle metabolic rate and mitochondrial metabolism in human muscle of sedentary vs. active individuals.Research Design and Methods:Chronic activity level was characterized by a physical activity questionnaire and a triaxial accelerometer as well as a maximal oxygen uptake test. The ATP and O2 fluxes and mitochondrial coupling (ATP/O2 or P/O) in resting muscle as well as mitochondrial capacity (ATPmax) were determined in vivo in human vastus lateralis muscle using magnetic resonance and optical spectroscopy on 24 sedentary and seven active subjects. Muscle biopsies were analyzed for electron transport chain content (using complex III as a representative marker) and mitochondrial proteins associated with antioxidant protection.Results:Sedentary muscle had lower electron transport chain complex content (65% of the active group) in proportion to the reduction in ATPmax (0.69 ± 0.07 vs. 1.07 ± 0.06 mm sec−1) as compared with active subjects. This lower ATPmax paired with an unchanged O2 flux in resting muscle between groups resulted in a doubling of O2 flux per ATPmax (3.3 ± 0.3 vs. 1.7 ± 0.2 μm O2 per mm ATP) that reflected mitochondrial uncoupling (P/O = 1.41 ± 0.1 vs. 2.1 ± 0.3) and greater UCP3/complex III (6.0 ± 0.7 vs. 3.8 ± 0.3) in sedentary vs. active subjects.Conclusion:A smaller mitochondrial pool serving the same O2 flux resulted in elevated mitochondrial respiration in sedentary muscle. In addition, uncoupling contributed to this higher mitochondrial respiration. This finding resolves the paradox of stable muscle metabolism but greater mitochondrial respiration in muscle of inactive vs. active subjects.